The United Nations and the Pacific Islands - Hassall, Graham (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book critically examines the relationship between the United Nations Organization and the small states of the Pacific islands. It provides an in-depth coverage of the United Nations, coupled with how Pacific Small Island Developing States interact. It covers three themes, the first one being the position of the UN on the Pacific Islands, which examines the role of the many UN organs, agencies and programs in strengthening individual countries and the region as a whole. It examines the manner in which the UN's activities have benefited Pacific nations, territories and peoples. The second theme deals with the Pacific states in the UN, and examines the participation of Pacific nations and territories in the UN's various organs, agencies, and programmes. It analyses the contribution they have made to the effectiveness of the organization, as distinct from the benefits they have sought to gain from it. The third and last theme deals with small states in global public policy, taking a broader look at how small states are faring within the UN system in the age of global discourse on shared public goods/public policy concerns.
Introduction: The Pacific Islands Region and the United Nations -- Part One: Self-determination and the development of new nations -- Self-Determination -- National development planning, implementation, and assessment -- Regional Development and the UN -- UN Offices in the Pacific -- Governance and Pacific Islands Policy networks -- Part Two: Pacific Islands engagement in the UN -- Membership and Participation in the major organs -- Regional Peace and Security -- Part Three: Small Island Developing Countries, Regionalism, and Global Multilateralism -- Global Policy Networks & Global Summitry -- Global Development Plans -- The Emergence of SIDS Development Discourse -- Small States as Good States, Smart States, in the Global Era.
Keywords: Political science; Biotechnology; Regionalism; Human rights; Political Science; Biotechnology; Regionalism; Human Rights